Photoionization Study on the 1s\(^{2}\)2snp \(^{1}\)P\(^°\), 1s\(^2\)2snd \(^{1,3}\)D, and 1s\(^{2}\)2pnd \(^{3}\)D, Rydberg Series of the Be-like \((Z=8-18)\) ions - Sakho, I. (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2021)
We report accurate Photoionization energies for the 1s22snp 1P°, 1s22snd 1,3D, and 1s22pnd 3D Rydberg series of the Be-like (Z = 8-18) ions. Calculations are done in the framework of the Screening constant per unit nuclear charge (SCUNC) method. The SCUNC predictions for n> 8 may be useful primary source for the NIST database. In addition, the present work enlighten the discrepancies between the MCDF results of Stancalie [Eur. Phys. J. D, 67, 223, (2013)] and the Opacity Project Team (OPT) predictions (the Opacity Project (IOPP, Vol.1, 1995) especially for the 1s22s9p 1,3D2 levels of the Al 9+ ions. The MCDF calculations are equal to - 0.60909 a. u (1s22s9p 1D2) and - 0.60663 a. u (1s22s9p 3D2). For these states, the OPT data are at - 0.61923 a. u (1s22s9p 1D2) and - 0.62020 a. u (1s22s9p 3D2). The present SCUNC calculations give for these levels -0.6179 a. u (1s22s9p 1D2) and -0.6205 a. u (1s22s9p 3D2). Numerous new data are tabulated as useful guideline for investigators focusing their researches on the Photoionisation of Be-like systems as far as the 1s22snp 1P°, 1s22snd 1,3D, and 1s22pnd 3D Rydberg series are concerned.